(untitled) (The Pakistan Development Review, 2025)
This paper investigates how Pakistani higher education students from different social strata act within the context of a game that allows for cooperation and punishment. Findings reveal that both female and male madrassa students are the most generous players. Moreover, there is more gender and social consciousness in male students than female students when deciding to penalise or not. Male madrassa students penalise female students more than male higher-income students; moreover, elite male students penalise male madrassa students more heavily than fellow elite students. The latter result suggests the presence of spite among elite boys towards high contributors if they belong to another social class/group. This research helps us break from social stereotypes that depict lower-income madrassa students as particularly intolerant of other social groups. JEL Classification: C71, C90, D91, Z12, Z13 Keywords: Higher Education, Madrassas, Public Goods Game, Social Stratification.